MHC class II-restricted antigen presentation is required to prevent dysfunction of cytotoxic T cells by blood-borne myeloids in brain tumors - Kilian, Michael; Sheinin, Ron; Tan, Chin Leng; Friedrich, Mirco; Krämer, Christopher; Kaminitz, Ayelet; Sanghvi, Khwab; Lindner, Katharina; Chih, Yu-Chan; Cichon, Frederik; Richter, Benjamin; Jung, Stefanie; et al. (Cancer cell, 2023)
Cancer immunotherapy critically depends on fitness of cytotoxic and helper T cell responses. Dysfunctional cytotoxic T cell states in the tumor microenvironment (TME) are a major cause of resistance to immunotherapy. Intratumoral myeloid cells, particularly blood-borne myeloids (bbm), are key drivers of T cell dysfunction in the TME. We show here that major histocompatibility complex class II (MHCII)-restricted antigen presentation on bbm is essential to control the growth of brain tumors. Loss of MHCII on bbm drives dysfunctional intratumoral tumor-reactive CD8+ T cell states through increased chromatin accessibility and expression of Tox, a critical regulator of T cell exhaustion. Mechanistically, MHCII-dependent activation of CD4+ T cells restricts myeloid-derived osteopontin that triggers a chronic activation of NFAT2 in tumor-reactive CD8+ T cells. In summary, we provide evidence that MHCII-restricted antigen presentation on bbm is a key mechanism to directly maintain functional cytotoxic T cell states in brain tumors.
Online verfügbar 12 January 2023, Version des Artikels 13 February 2023
Gesehen am 26.01.2023